Delivery room management of extremely preterm infants: the EPIPAGE-2 study. Issue 5 (2nd February 2016) - Perlbarg, J; Ancel, P Y; Khoshnood, B; Durox, M; Boileau, P; Garel, M; Kaminski, M; Goffinet, F; Foix-L'Hélias, L; ,
Abstract : Objective: To analyse the delivery room management of babies born between 22 and 26 weeks of completed gestational age and to identify the factors associated with the withholding or withdrawal of intensive care. Study design: Population-based cohort study. Patients and methods: Our study population comprised 2145 births between 22 and 26 completed weeks enrolled in the EPIPAGE-2 study, a French cohort of very preterm infants born in 2011. The primary outcome measure was withholding or withdrawal of intensive care in the delivery room. Results: Among infants born alive at 22–23 weeks, intensive care was withheld or withdrawn for >90%. At 24 weeks, resuscitative measures were withheld or withdrawn for 38%, at 25 weeks for 8% and at 26 weeks for 3%. Other factors besides gestational age at birth associated with this withholding or withdrawal for infants born at 24–26 weeks were birth weight <600 g, emergency delivery (within 24 h of the mother's admission) and singleton pregnancy. Although rates of withholding or withdrawal of intensive care varied substantially between maternity units (from 0% to 100%), the variability was primarily explained by differences in distributions of gestational age at birth. Conclusions: Although gestational age is only one factor predicting survival of preterm infants, practices in France appear to be based primarily on this factor, which thus has direct effects on the survival of extremely preterm infants. The ethical implications of basing life and death decisions only on gestational age before 25 weeks require further examination.